Strategic analysis of Porsche AG : luxury EV market - Serhiienko, Yevhenii; Bruder Badie, Natálie; Machek, Ondřej, 1985-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
Electric vehicles have become the backbone of sustainable transportation in the rapidly evolving automotive world. The luxury electric vehicle segment, particularly, is seeing significant growth, with high-end manufacturers vying for market dominance. This thesis examines in detail the strategic positioning of Porsche AG, a renowned luxury car manufacturer, in the luxury electric vehicle market. The company's competitive advantages and potential challenges are examined by a comprehensive analysis of Porsche's strategic initiatives. The study uses various strategic tools, including SWOT analysis, Porter's Five Forces, and PEST analysis, to provide a holistic view of Porsche's position in the luxury electric vehicle ecosystem. The thesis concludes with practical recommendations for Porsche AG management to strengthen its position in the luxury electric vehicle segment.
Vedoucí práce: Natálie Bruder Badie
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses